Tectonic influence on SE Asian carbonate systems and their reservoir quality - Wilson, Moyra; Hall, R. (Society for Sedimentary Geology, Special Publication 95, 2010)
SE Asian carbonate formations have been reviewed with the aim of understanding the influence of tectonics on their development and reservoir potential through the Cenozoic. Regional tectonics, via plate movements, extensional basin formation, and uplift, was the dominant control on the location of carbonate deposits. These processes controlled the movement of shallow marine areas into the tropics, together with their emergence and disappearance. Although ~ 70% of the 250 shallow marine carbonate formations in SE Asia were initiated as attached features, 90% of economic hydrocarbon discoveries are in carbonate strata developed over antecedent topography, of which more than 75% were isolated platforms. Faulted highs influenced the siting of nearly two thirds of carbonates developed over antecedent topography. Around a third of carbonate units formed in intra- and interarc areas; however, economic reservoirs are mainly in backarc and rift-margin settings ( ~ 40% each). Carbonate edifices show evidence of syntectonic sedimentation through: (1) fault-margin collapse and resedimentation, (2) fault segmentation of platforms, (3) tilted strata and differential generation of accommodation space, and (4) modification of internal sequence character and facies distribution. The demise of many platforms, particularly those forming economic reservoirs, was influenced by tectonic subsidence, often in combination with eustatic sea-level rise and environmental perturbations. Fractures, if open or widened by dissolution, enhance reservoir quality. However, fracturing may also result in compartmentalization of reservoirs through formation of fault gouge, or fault leakage via compromised seal integrity. This study will help in reservoir prediction in complex tectonic regions as the petroleum industry focuses on further exploration and development of economically important carbonate reservoirs.